A conceptual model of the multiple stages of communication necessary to support patient-centered care. (July 2013) - Halley, Meghan C; Rendle, Katharine AS; Frosch, Dominick L
Patient-centered care requires that both healthcare providers and patients have access to comparative effectiveness research (CER), which provides direct comparisons of the risks and benefits of available clinical options. However, insufficient attention has been paid to developing the comprehensive communication systems necessary to ensure that CER reaches patients and healthcare providers. In this review, we propose a model of the multiple stages of CER communication necessary for patient-centered care and review the existing research and gaps in knowledge relevant to each stage. These stages include: promotion of the underlying concepts and value of CER; translation of CER results; dissemination of CER results; and utilization of the results of CER in shared decision-making between patients and providers. A comprehensive approach to CER communication is necessary to ensure that the growing interest in and availability of CER is able to support a more patient-centered model of healthcare.